Introduction to Multidisciplinary Clinics and Their Value - Owens, Winston R.; Schmidt, Josephine L.; Hollier, Pierce C.; Cole, Sam H.; Buchanan, Edward P.; Ching, Jessica A. (Seminars in Plastic Surgery, 2025)
Multidisciplinary clinics (MDC) are a mainstay in medical and surgical management of complex diseases in the adult and pediatric populations. Due to increasingly complicated multimodal treatment plans and difficulties coordinating care, MDCs emerged to simplify care administration for patients and providers while optimizing outcomes. Multidisciplinary care is delivered in a variety of ways; however, the most common setups are concurrent and sequential clinics. With proper personnel and infrastructure organization, MDCs are beneficial to patients, providers, and institutions both clinically and financially. This introductory article will describe a brief history of MDCs, different models of operation, and known clinical and financial gains.
Keywords: multidisciplinary clinics; multidisciplinary team; cost-efficient; value; MDC; MDT